57.1k views
18 votes
Solve the equation. 5t^3 +40t^2 = -80t

User TauzN
by
5.0k points

1 Answer

2 votes

Answer:

-5t2 + 40t - 3

Explanation:

Step-1 : Multiply the coefficient of the first term by the constant 5 • 3 = 15

Step-2 : Find two factors of 15 whose sum equals the coefficient of the middle term, which is -40 .

-15 + -1 = -16

-5 + -3 = -8

-3 + -5 = -8

-1 + -15 = -16

1 + 15 = 16

3 + 5 = 8

5 + 3 = 8

15 + 1 = 16

User Nikita Patil
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.